A Comparative Assessment Study on Natural Coagulant and Regenerated Coagulant - Alok Suman (Journal of Global Pharma Technology, 2020)
Surface water brings impurities in the form of suspended and colloidal solids. Coagulation and ﬂocculation followed by ﬁltration and disinfection process involved in the treatment of surface water. This process generates large quantity of waste generally known as water treatment sludge (WTS). A typical Water Treatment Plant (WTP) produces about 100,000 tons/year of sludge whereas, on a global scale, available literature estimates that at present the daily production of sludge exceeds 10,000 tons (Babatunde and Zhao, 2007). Increase in demand for milk and dairy products, dairy industries in most of the countries of the world, including India will lead to enhanced productivity, as a result increase in wastewater generation and environmental pollution. The objective of the present study is to determine WTS characteristics obtained from WTP and to investigate the reuse of recovered/regenerated coagulant in synthetic dairy effluent and compare with natural coagulant (Moringa Oleifera Seed Powder (MOSP)). The characterization of WTS shows the maximum amount of SiO2   at 67.75% by using Energy-Dispersive X-Ray Fluorescence (ED-XRF). The other oxides also observed by ED-XRF such as Al2O3 (16.76%), Fe2O3 (5.52%) and MgO (3.33%). For the optimum recovery of the coagulant, WTS acidified with the different normality of sulfuric acid. The RC produced similar turbidity removal efficiency (94%) at 25ml/l dose as compared to natural coagulant at 60 ml/l dose. It also has been observed that the removal of TSS, TDS, BOD and COD efficiently by RC. CPCB [3] reported that some of the WTPs are cleaned once in a year and in the lack of sludge disposal management it disposed off on nearby open lands or drain. Proper handling WTS from WTPs in an economical and environmentally friendly manner remains a very important issue. The recovery, recycling and reuse may provide a sustainable solution to the WTS management.Keywords: Water Treatment, Sludge, Recovery of coagulant, MOSP, SEM, ED-XRD, FTIR, and XRD.